The Significance of Federal Taxes as Automatic Stabilizers - Di Bella, Gabriel (IMF Working Papers; Working Paper, 2002)
In this paper, a simple methodology to assess the effectiveness of automatic stabilizers is proposed and empirically tested using French data for the period 1970-2000. The paper concludes that fiscal stabilizers have dampened output variability by approximately 35 45 percent depending on the measure of potential output used. In addition, the results indicate that fiscal stabilizers mainly operated through the reduction of private investment fluctuations from 1970 to 1985, and through the reduction of private consumption variability thereafter. Due to the counterfactual nature of the analysis performed, the simplicity of the theoretical model, and simultaneity issues that might introduce biases, the results can at most be interpreted as approximations of the phenomenon that is analyzed.